Problem solving skill: Effectiveness on think pair share with comic - Isti Dwi Mustafia; Sri Adi Widodo (International Journal on Teaching and Learning Mathematics, 2018)
The purpose of this study was to determine the effectiveness of the Think Pair Share with the comic of 7th grade students’ ability to solve mathematical problems in SMP 9 Yogyakarta. This type of research is an experiment with posttest-only-control design. The sample used in the study determined by cluster random sampling technique. The results of hypothesis testing using the t-test showed that tcount is greater than ttable, in other words, Think Pair Share learning with comic generates better mathematical problem solving skills to students than think pair share only. Furthermore, Think Pair Share with the comic is more effective when viewed from the ability to solve problems.